The Diversity of the Pollen Tube Pathway in Plants: Toward an Increasing Control by the Sporophyte - Lora, Jorge; Hormaza, José I.; Herrero, María (Frontiers in Plant Science, 2016)
Plants, unlike animals, alternate multicellular diploid and haploid generations in their life cycle. While this is widespread all along the plant kingdom, the size and autonomy of the diploid sporophyte and the haploid gametophyte generations vary along evolution. Vascular plants show an evolutionary trend towards a reduction of the gametophyte, reflected both in size and lifespan, together with an increasing dependence from the sporophyte. This has resulted in an overlooking of the importance of the gametophytic phase in the evolution of higher plants. This reliance on the sporophyte is most notorious along the pollen tube journey, where the male gametophytes have to travel a long way inside the sporophyte to reach the female gametophyte. Along evolution, there is a change in the scenery of the pollen tube pathway that favors pollen competition and selection. This trend, towards apparently making complicated what could be simple, appears to be related to an increasing control of the sporophyte over the gametophyte with implications for understanding plant evolution.